Nivolumab in chemotherapy-resistant cervical cancer: report of a vulvitis as a novel immune-related adverse event and molecular analysis of a persistent complete response. Issue 1 (31st October 2019) - Baettig, Florence; Vlajnic, Tatjana; Vetter, Marcus; Glatz, Katharina; Hench, Jürgen; Frank, Stephan; Bihl, Michel; Lopez, Roberto; Dobbie, Michael; Heinzelmann-Schwarz, Viola; Montavon, Céline
Abstract : Background: Treatment options for advanced cervical cancer are limited and patients experiencing recurrence after first-line cisplatin-based chemotherapy and bevacizumab have a poor prognosis. A recent phase II study in advanced cervical cancer has demonstrated a disease control rate of 68.4% with the immune checkpoint inhibitor nivolumab. By blocking immune checkpoints, immunotherapy puts the immune system into a state of hyper-activation that can cause immune-related adverse events. We present the clinical, pathological and molecular data of a patient with metastatic cervical cancer and progressive disease after second-line therapy. We report on the therapeutic response under third-line immunotherapy with nivolumab, the immune-related adverse events (IRAE), and their successful management. Case presentation: We report the case of a 62-year-old woman who was diagnosed with advanced squamous cell carcinoma of the cervix with paraaortic lymph node metastases. After an initial combined radio-chemotherapy with cisplatin, she developed local and nodal (supraclavicular) recurrence. Second-line chemotherapy with 6 cycles of carboplatin, paclitaxel, and bevacizumab resulted in a partial response for 6 months. Checkpoint inhibition with nivolumab was started due to progression, leading to persistent complete remission. Immunotherapy was well tolerated for 8 months until the patient presented with an immune-related isolated vulvitis, which was successfully managed with topical corticosteroids. Conclusions: The persistent complete response after third-line treatment for relapsed chemotherapy-resistant cervical cancer presented in this case highlights the potential of immunotherapy for patients with advanced cervical cancer impressively. To our knowledge, this is the first report of an isolated immune-related vulvitis under nivolumab. This adverse event might be underdiagnosed and mistreated, however, it is of importance due to its impact on quality of life, sexual wellbeing and compliance of patients. Successful IRAE management may enable prolonged immune checkpoint inhibitor therapy. In the future, routine molecular tumour profiling is likely to aid in the stratification of cervical cancer patients for immunotherapy. Here, we provide the methylome data of a case with complete response.